Differential diagnosis of neonatal cholestasis by genetic testing: A case report - Sakura Kawahara; Kazuo Imagawa; Shusuke Takeuchi; Tomoya Iwasaki; Yuki Okada; Yuri Nakamura; Shogo Saito; Takato Sasaki; Kouji Masumoto; Hidetoshi Takada (Elsevier, 2023)
Introduction: Alagille syndrome (ALGS) is a cholestasis disorder with multiple organ dysfunction, including heart and kidney. The causative genes of ALGS are JAG1 and NOTCH2. Dysregulation of Notch signaling leads to defects in the developmental mechanisms of the bile ducts. Sometimes extrahepatic bile duct hypoplasia makes it difficult to differentiate ALGS from biliary atresia. The Kasai procedure for ALGS is associated with poor liver and patient outcomes. Therefore, it is important to differentiate ALGS from biliary atresia correctly. Case presentation: A 2-day-old female neonate was admitted to the neonatal intensive care unit due to poor feeding; blood tests on day 7 showed elevated direct bilirubin and total bile acids. Right hydronephrosis, peripheral pulmonary artery stenosis, butterfly vertebra, and posterior embryotoxon were observed, and ALGS was suspected from these findings. Duodenal fluid tests and biliary scintigraphy showed no bile excretion from the liver into the intestinal tract. These findings suggested biliary atresia, and to distinguish ALGS from biliary atresia, rapid JAG1 and NOTCH2 sequencing was performed preoperatively. We found a heterozygous de novo single nucleotide insertion mutation c.192dupC p.(Lys65GlnfsX8). Operative cholangiography showed that the common bile duct was patent, but the common hepatic duct was barely open, a finding consistent with type III-a-o biliary atresia. Because of the preoperative diagnosis of ALGS, Kasai procedure was omitted. Conclusion: Neonates and early infants with cholestasis with extrahepatic symptoms should be carefully examined, with genetic syndromes and biliary atresia considered differential diagnoses. Advances in genetic analysis methods are expected to facilitate early diagnosis of ALGS.